2022
DOI: 10.4103/ajps.ajps_110_20
|View full text |Cite
|
Sign up to set email alerts
|

Management of Trichobezoar

Abstract: Background: Trichobezoar is an uncommon clinical entity in which ingested hair mass accumulates within the digestive tract. It is generally observed in children and young females with psychological disorders. It can either be found as an isolated mass in the stomach or may extend into the intestine. Untreated cases may lead to grave complications. Material and Methods: We retrospectively analyzed the clinical data of six patients treated for trichobezoar in Monastir ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Bezoars typically develop in the stomach and occasionally in the small intestine. [ 1 ] They are usually classified into phytobezoars (plant material), trichobezoars (hair), lactobezoars (milk), and pharmacobezoars (medications) according to their composition. [ 2 ] Trichobezoars are the accumulation and impaction of ingested hairs in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bezoars typically develop in the stomach and occasionally in the small intestine. [ 1 ] They are usually classified into phytobezoars (plant material), trichobezoars (hair), lactobezoars (milk), and pharmacobezoars (medications) according to their composition. [ 2 ] Trichobezoars are the accumulation and impaction of ingested hairs in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Trichobezoars are the accumulation and impaction of ingested hairs in the gastrointestinal tract. [ 1 , 2 ] They often result from continuous and prolonged habitual ingestion of human hair as well as fur from dolls, animals, and blankets. Trichobezoars are usually retained in the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, there were no reported psychiatric or gastrointestinal surgery histories as common risk factors for bezoar formation [ 4 , 5 , 9 ]. Dietary habits included excessive consumption of fruits or vegetables in 24.4 % of the cases and accidental ingestion of metallic objects in 17 % of the cases.…”
Section: Risk Factorsmentioning
confidence: 97%